Deglacial history of glacial lake windermere, UK: implications for the central British and Irish Ice Sheet. (19th December 2012) - Pinson, Luke J. W.; Vardy, Mark E.; Dix, Justin K.; Henstock, Timothy J.; Bull, Jonathan M.; Maclachlan, Suzanne E.
Abstract In the UK, a combination of outcrop mapping, satellite digital elevation models, high‐resolution marine geophysical data and a range of dating techniques have constrained the maximum limit and overall retreat behaviour of the British and Irish Ice Sheet (BIIS). The changing styles of deglaciation have been most extensively studied in the west and north‐western sectors of the BIIS, primarily using offshore geophysical surveys. The surviving record in the southern, terrestrial sector is fragmentary, permitting only large‐scale (tens of kilometres) and longer timescale (c. 1 ka) reconstructions of ice‐margin movement, with limited information on deglacial processes. Here we present a high‐resolution study of the retreat behaviour for a section of the southern ice‐margin from Windermere in the Lake District, using high‐resolution two‐dimensional multi‐channel seismic data, processed using prestack depth migration. By combining the seismic stratigraphy with landform morphologies, extant cores and seismic velocity measurements, we are able to distinguish between: over‐consolidated till; recessional moraines; De Geer moraines; flowed till/ice‐front fan; supra‐/en‐glacial melt‐out till; and subsequent glaciolacustrine/lacustrine sedimentation. The results reveal a complex and active valley glacier withdrawal from Windermere that changed character between basins and produced two small, localized areas of ice‐stagnation and downwasting. This study indicates that similar active ice‐margin retreats probably took place in other valleys of the Lake District during the Late Devensian deglaciation rather than the previously held view of rapid ice‐stagnation and downwasting. When combined with the regional terrestrial record, this supports a model of early ice loss in terrestrial England compared with other parts of the UK. Copyright © 2012 John Wiley & Sons, Ltd.